Chronic idiopathic musculoskeletal pain in youth: a qualitative study - Hervé Lefèvre; Alexandra Loisel; Brigitte Bader Meunier; Chantal Deslandre; Noémie Lemoine; Marie Rose Moro; Pierre Quartier; Jonathan Lachal (BMC, 2019)
Abstract Background Chronic musculoskeletal pain (MSP) is frequent in adolescents and has major medical and social consequences. In many cases, when no cause has been clearly established, this pain may be considered to be chronic idiopathic MSP. Our study seeks to identify general criteria for this type of pain through the experience of professionals from tertiary care centers with expertise in pediatric and adolescent chronic MSP. Methods Cross-sectional multicenter qualitative study. Semi-structured interviews of 25 professionals at a rheumatology reference center and in its network for pain management, including diverse specialists and professions. Interpretative Phenomenological Analysis is used to explore the data. Results This approach led us to identify 10 themes organized around three superordinate themes covering different stages of the diagnostic process: 1) the medical pain history up to the consultation at the reference center; 2) the professional's subjective feelings about the clinical presentation; 3) from the clinical examination to diagnosis and treatment of chronic idiopathic MSP. The main elements guiding this diagnosis do not come from the physical examination but from the medical history and the professionals' subjective feelings, that is, their clinical judgment. The professionals' impression of uneasiness and frustration, induced by patients and their parents, is of major importance. Conclusion The principal elements guiding the diagnosis of chronic idiopathic MSP do not come primarily from the physical examination but rather from the pain history and the health professional's subjective feelings. Our results suggest that the concept of Juvenile Fibromyalgia (JFM) does not appear to cover all situations of chronic idiopathic MSP in adolescence. A constellation of non-organic criteria enables diagnosis of the latter; these criteria should be validated to avoid medical nomadism and multiple investigations and to shorten the interval until patients receive optimal pain management. Clinical trial registration clinicaltrials.gov, NCT03171792, https://clinicaltrials.gov/ct2/show/NCT03171792?term=LACHAL&cntry=FR&city=paris&rank=1